(untitled) (Experimental biology, 2018)
One of the priority areas of modern environmental research is the development of theoretical and practical aspects of the bioremediation of water bodies, based on the use of natural mechanisms for self-purification and self-recovery of water bodies, the action of which is related to the activity of microorganisms belonging to different types of cyanobacteria and microalgae. It is known that in order to increase the efficiency of bioremediation, not mono-but mixed cultures of microorganisms are used to obtain which it is necessary to take into account the peculiarities of intraspecific relationships between cyanobacteria and microalgae and the interference of photo- and heterotrophic microorganisms. The aim of the research was to study the mutual influence of the species of higher aquatic plants (HAP), cultures of cyanobacteria and microalgae resistant to heavy metals to form associations of them in model experiments. By results of researches, cultures for creation of consortium HAP with phototrophic microorganisms, perspective for bioremediation are selected. It was found that the ability to co-exist in the Pistia stratiotes was observed from cultures of cyanobacteria Phormidium autumnale I-5 and Anabaena variabilis RI-5 from the studied higher aquatic plants. It is determined that of the studied microalgae species of Ankistrodesmus sp. BI-1 and Schenedemus quadricauda B-1 can be consortia of the higher aquatic plant Pistia stratiotes.